STUDI ANALISIS PEMODELAN BANGKITAN DAN TARIKAN LALU LINTAS (STUDI KASUS : SMAN 1 TAMAN DAN SMPN 2 TAMAN SIDOARJO) - Handriyadi, Mokhammad Rahisa; Sarya, Gede; Rizkiardi, Aditya; Trimurtiningrum, Retno (EXTRAPOLASI, 2020)
AbstractIndonesia is an enormous country, it has about 266.91 million people. By the increment of population, it also affects the number of vehicles. However, it does not compensate by constructing the road, which causes congestion and production activation at school, industry, etc. This research purpose is to analyze the production and attraction at State High School 1 of Taman and Junior High School 2 of Taman – Sidoarjo.From the result, it can be seen that the production and attraction at State High School 1 of Taman and Junior High School 2 of Taman – Sidoarjo for motorcycle, the correlation test (r) is 1 and the Regression test is Y = 42.7142 + 0.2857 X of 112 teachers, for the shuttle the correlation test is 0.1 and the simple test Regression is Y = 1103.80 + 236 X of 2333 students, for public transportation the correlation test (r) is 1 and the simple test Regression is Y = 891.66 + 32.3 X of 2333 students. The maximum traffic volume occurs on Monday at 6.30 to 7.30 a.m. for Surabaya direction is 3923 vehicle/hour and Sidoarjo direction is 2276 vehicle/hour, and for degree saturation is obtained 0,97.AbstrakIndonesia adalah negara yang sangat besar, memiliki sekitar 266,91 juta penduduk. Dengan meningkatnya populasi orang, sangat mempengaruhi jumlah kendaraan. Namun, itu tidak diimbangi dengan pembangunan jalan, yang menyebabkan kemacetan dan aktivasi produksi di sekolah, industri, dll. Tujuan penelitian ini adalah untuk menganalisis bangkitan dan tarikan di SMA Negeri 1 Taman dan SMP 2 Taman – Sidoarjo.Dari hasil penelitian, dapat diketahui bahwa bangkitan dan tarikan pada SMA Negeri 1 Taman dan SMP 2 Taman - Sidoarjo untuk sepeda motor, uji korelasi (r) adalah 1 dan uji Regresi adalah Y = 42.7142 + 0,2857 X dari 112 guru, untuk antar jemput tes korelasi adalah 0,1 dan tes sederhana Regresi adalah Y = 1103,80 + 236 X dari 2333 siswa, untuk transportasi umum tes korelasi (r) adalah 1 dan tes sederhana Regresi adalah Y = 891,66 + 32,3 X dari 2333 siswa. Volume lalu lintas maksimum terjadi pada hari Senin pukul 6.30 hingga 7.30 pagi untuk arah Surabaya adalah 3923 kendaraan / jam dan arah